Potential of Mainstay Debit of Lematang River, South Sumatra for the Regional Planning for Irrigation at Dongku and Modong - Syariman, Petrus; Kustaman, Kustaman (Forum Geografi, 1999)
District Muara Enim, South Sumatra Province has a potential region to develop an agriculture sector especially rice fields. The water resource such as Water Enim and Lamatang River support the capacity of the developing. Acording to the study in 1985 carried out by the BCEOM and Kampsax consultants, the lower Lematang region. Dangku Kiri, Dangku Kanan, and Modong with the total area of about 10.000 Ha has a highly potential to built rice field ith the technical irrigation. Based on the information, research of dependable flow of Lematang River to the irrigation requirement had been carried out by analyzing of all data collecting in those areaÂ  such as rainfall, climate, and discharge data. The result shows that the dependable flow of 20% probability of non exceedence is about 65.3 m3/sec. It is potential enough compare with the irrigation requirement of about 1.85 l/sec/ha or 18.5 m3/sec of total irrigation area. Technically, dependable flow of Lematang River is big enough but some constraints will appear especially in determining of free intake or weir because the river gradient is too low and the mainÂ  channel has been used by the people for navigation. To increase the accuracy of the research, an Automatic Water Level Recorder and one climatological station should be installed respectively in the alternative I location and in the irrigation area.